Closed-Loop Crop Cascade to Optimize Nutrient Flows and Grow Low-Impact Vegetables in Cities - Rufí-Salís, Martí; Parada, Felipe; Arcas-Pilz, Verónica; Petit-Boix, Anna; Villalba, Gara; Gabarrell, Xavier (Frontiers in Plant Science, 2020)
Urban agriculture systems can significantly contribute towards mitigating the impacts of complex food supply chains and increase urban food sovereignty. Improving these facilities in terms of nutrient management can lead to better practices and environmental performance. Based on a rooftop greenhouse in the Barcelona region, we propose a cascade system where the leachates of tomato cycle (donor crop) are used as the main irrigation source for five successive lettuce cycles (receiving crop). By determining the agronomic performance and the nutrient metabolism of the system, we aim to define the potential of these systems to avoid nutrient depletion and mitigate eutrophication, while scaling the system in terms of nutrient supply between the donor and the receiving crops. The results show that low yields (below 130g per lettuce plant) are obtained if a cascade system is used during the early stage of the donor crop, as the amount of nutrients in donor’s leachates, specially N (62.4 mg irrigated per plant in the first cycle), is not enough to feed the lettuce receiving crop. This effect is also observed in the nutrient content of the lettuce, which increases with every test until equaling the control (4.4% of N content) as the leachates got richer, although unsuitable electrical conductivity values (near 3 dS/m) are reached at the end of the donor crop cycle. Findings on the uptake of the residual nutrient flows show how the cascade system was able to take advantage of the nutrients to produce local lettuce while mitigating the effect of N and P in the freshwater and marine environments. Considering our case study, we finally quantified the scale between the donor and receiving crops and propose three major ideas to optimize the nutrient flows while maintaining the yield and quality of the vegetables produced in the receiving crop.